ENHANCED DNA EXTRACTION FROM TRIGONA HONEY: A LOW-VOLUME OF SAMPLE, HIGH-PURITY APPROACH FOR MOLECULAR RESEARCH - Gultom, Endang Sulistyarini; Rini Hafzari; Melva Silitonga; Eva Sartika Dasopang (Polish Journal of Natural Sciences, 2025)
Bees synthesize honey from floral nectar, with pollen inadvertently incorporated during the foraging process. Pollen constitutes the primary source of plant DNA in honey; however, its extraction is impeded by the high concentrations of sugars, phenolic compounds, and carbohydrates, often resulting in low purity and necessitating substantial sample volumes. This study presents a modified DNA extraction technique specifically optimized for Trigona honey, aimed at enhancing both efficiency and practicality. The protocol involves a pretreatment step where honey is diluted in a 1:4 ratio with distilled water, incubated at 60 °C for 25 minutes, followed by extraction without sample destruction. The quality of the extracted DNA was assessed using a nano spectrophotometer and PCR, demonstrating a high concentration of 1,790 ng/μL with distinct, smear-free bands. This method is straightforward, time-efficient, and resource-conserving, rendering it highly applicable for molecular research and honey authentication.